Additional evidence on transparency and bank financial performance. Issue 1 (19th September 2016) - Akhigbe, Aigbe; McNulty, James E.; Stevenson, Bradley A.
Abstract: Transparency expands the market for a firm's stock and lowers the cost of capital. Previous research measures bank transparency by analyst following and the standard deviation of analyst earnings per share forecasts and finds that transparency has a positive effect on bank financial performance. An earlier theoretical study in the market micro structure literature suggests that return volatility and trading volume are important measures of transparency. We examine the relation between transparency and bank holding company (BHC) profit efficiency using these four measures of transparency for 1996 through 2014. Our two stage least squares regression analysis indicates that transparency has a positive effect on bank financial performance. This is not a size effect as the result holds in each of three size categories. This is an important finding given that the recent financial crisis was characterized by a lack of transparency at a number of banking institutions.